Acceptability of an economic support component to reduce early pregnancy and school dropout in Zambia: a qualitative case study. Issue 1 (1st January 2019) - Banda, Emmanuel; Svanemyr, Joar; Sandøy, Ingvild Fossgard; Goicolea, Isabel; Zulu, Joseph Mumba
ABSTRACT: Background : Cash Transfer (CT) schemes have become popular poverty reducing measures in many low and middle-income countries. Research indicates that when provided to girls in resource poor settings, cash transfers can increase education and postpone marriage and pregnancy. However, a few studies indicate that they can also have negative effects which can affect their acceptability, such as generating intra-community tensions. Objective : Conceptually informed by Rogers' diffusion of innovation theory, this paper explores factors affecting the acceptability of economic support in a randomized controlled trial in rural Monze and Pemba Districts of Southern Province in Zambia. Methods : Qualitative data were collected through five focus group discussions and six in-depth, semi-structured interviews and analysed using thematic analysis. This study was done in the combined arm of a trial where girls received both economic support and participated in youth clubs offering sexuality and life-skills education. Results : In the study communities, acceptability was encouraging by the belief that economic support provided benefits beyond beneficiaries and that it improved access to education, and reduced teen pregnancies, marriages and school drop-out. However, provision of economic support only to selected girls and their parents and fear among some that the support was linked to satanic practices negatively affected acceptability. These fears were mitigated through community sensitisations. Conclusion : The study demonstrated that relative advantage, observability, simplicity and compatibility were key factors in influencing acceptability of the economic support. However, to enhance acceptability of cash transfer schemes aimed at addressing early marriage and pregnancy, it is important to explore socio-cultural factors that create suspicions and negative perceptions and to provide schemes that are perceived as relatively better than available similar schemes, understood, compatible and viable beyond the immediate beneficiary.